Comparative Efficiency of Different Fat Replacers to Develop Functional Low Fat Carabeef Cookies - Goswami, Meena; Sharma, B. D.; Mendiratta, S. K.; Pathak, Vikas; Sharma, Heena (Journal of Meat Science, 2019)
The present study was carried out to develop functional low fat carabeef cookies with incorporation of different fat replacers viz. Poppy seeds, dried plum pulp powder and guar gum separately at 0.5-1.5% levels to replace 20-40% hydrogenated vegetable fat. The optimum level of each fat replacer was selected as carabeef cookies incorporated with 0.5% poppy seeds powder to replacer 20% fat (PO), car abeef cookies incorporated with 1.5% guar gum powder to replace 40% fat (GT ) and carabeef cookies incorporated with 1.0% plum pulp powder to replace 30% fat (PL). These selected levels of each fat replacer were further compared to select the best treatment Final experiment was conducted to evaluate the comparative efficacy of these fat replacers on the basis of various physic-chemical properties and sensory evaluation. There was significant difference (P<0.05) in between treatments for all physico-chemical properties except thick ness of cookies. Cooking yield, moisture, protein and ash percentage were significantly higher (P<0.05) in GT than other treatments. The pH of PL cookies was significantly lower (P<0.05) than PO cookies. Diameter and spread ratio were significantly higher (P<0.05) in PO, but no significant difference was observed in guar gum and plum pulp powder incorporated carabeef cookies. The color and appearance, crispiness and overall acceptability scores were significantly higher (P<0.05) in GT than PO and PL. The hardness and shear force value were significantly higher (P<0.05) at 1.5% guar gum level. Redness and hue angle were significantly higher (P<0.05) in plum pulp powder incorporated cookies than other treatments. Therefore, GT- carabeef cookies incorporated with 1.5% guar gum to replacer 40% hydrogenated vegetable fat were taken as the most desirable and acceptable treatment.